Platelet Indices and Hypertension: Results from Shahedieh Cohort Study, Yazd, Iran - Fateme Shakeri Shamsi; Moslem Taheri Soodejani (International Journal of Hypertension)
Introduction. Hypertension is one of the most important diseases worldwide. In this study, we aim to demonstrate the relationship between platelet indices and hypertension. Materials and Methods. We studied 9448 people in the age range of 30 to 70 years. We assessed their hypertension status, platelet count (PLT), mean platelet volume (MPV), platelet distribution width (PDW), smoking, cardiovascular disease history, diabetes status, body mass index, and creatinine levels. Hypertension status was assessed qualitatively. All platelet indices were categorized by quartiles. We then used logistic regression to predict the relationship between these indices and hypertension. Results. PDW index and hypertension had a statistically significant relationship in the second quartile (16.2 fL < PDW ≤ 16.7 fL) in 30 to 40 years old (AOR: 0.225, 95% CI: 0.063–0.806), in the fourth quartile in 50 to 60 years old (AOR = 1.532, 95% CI: 1.048–2.238), and in all the quartiles of the age range of over 60 years. PLT index had a positive relationship (AOR = 3.147, 0.95% CI: 1.163–8.516) in 30 to 40 years old in the fourth quartile vs. the first quartile. A positive relationship was obtained in the third and fourth quartiles of PLT and the age range of 40 to 50 years, respectively (AOR = 2.063, 0.95% CI: 1.162–3.662) and (AOR = 2.204, 0.95% CI: 1.220–3.981). Conclusion. According to the results of this study, some platelet indices could be correlated with hypertension, so we may be able to reduce the burden of this disease.